2002
DOI: 10.1002/ajim.10055
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pulmonary fibrosis after severe exposure to welding fumes

Abstract: While epidemiological data are limited, it is reasonable to conclude that a causal relationship exists between IPF in welders with long term exposure to high concentrations of welding fumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 33 publications
3
27
0
2
Order By: Relevance
“…Our findings are in line with these studies. Exposure to iron fumes or dust may give rise to siderosis, an accumulation of iron in the lungs (14,22,23), interstitial pulmonary fibrosis, or siderofibrosis (24), which have been suspected to be associated with an increased risk of lung cancer (25,26). IARC has defined welding fumes as possibly carcinogenic to humans (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with these studies. Exposure to iron fumes or dust may give rise to siderosis, an accumulation of iron in the lungs (14,22,23), interstitial pulmonary fibrosis, or siderofibrosis (24), which have been suspected to be associated with an increased risk of lung cancer (25,26). IARC has defined welding fumes as possibly carcinogenic to humans (27).…”
Section: Discussionmentioning
confidence: 99%
“…For each worker, the list of tasks and materials resulting in potential exposures to asbestos and silica was reviewed, as these were the primary exposures likely related to the risk of pneumoconiosis among these workers. Welding/cutting fume exposures also were reviewed as some studies have shown intense welding exposures to be associated with an increased risk of interstitial pulmonary fibrosis [Buerke et al, 2002]. In many instances, a worker reported multiple tasks or materials, which would generate an exposure.…”
Section: Descriptive and Stratified Analysesmentioning
confidence: 99%
“…Therefore, the observed acceleration in mortality resulting from PM 1648 or PM 2.5 exposure was not due to renal failure. However, pulmonary toxicity and fibrosis have been reported with urban particles with the greatest toxicity seen with PM 2.5 (Churg and Brauer, 2000;Schwartz and Neas, 2000;van Zijverden et al, 2001;Buerke et al, 2002). Also, there has been a consistent link between increased incidence of mortality and morbidity due to cardiopulmonary complications and elevated levels of particulate matter in the air (Salvi et al, 1999;Kleinman et al, 2000;Huang, Hsu, and Chan, 2003;Pozzi et al, 2003).…”
Section: Discussionmentioning
confidence: 98%